Changes in social support and the emotional health of immigrant, refugee, and non-immigrant children across middle childhood: A three year follow up study. - Kimberly Thomson; Carly Magee; Monique Gagne Petteni; Anne Gadermann (International Journal of Population Data Science, 2022)
Objectives Children who are new to Canada have unique circumstances that can be associated with their emotional health. Using linked immigration and child self-report data, we examined associations between changes in children’s social support and emotional health from ages 9 to 12, for immigrant, refugee, and non-immigrant children.